2017
DOI: 10.1017/s1352465817000662
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioural Therapy Competency: Pilot Data from a Comparison of Multiple Perspectives

Abstract: Raters differed in competency ratings. Implications for potential use and adaptation of CBT competency measurement methods to enhance training and implementation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…These findings have important implications regarding the use of self-evaluation as a resourceefficient CBT competence assessment methodparticularly in training. The changing proportion of agreement across training supports previous assertions that self-evaluation is not an appropriate stand-alone competence assessment for trainees (Rozek et al, 2018). Rather, selfassessment appears to be more appropriate as a self-reflective learning tool (Waltman et al, 2016), with trainees' understanding of their own skill becoming more accurate with repeated comparison to expert ratings and with increasing experience.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…These findings have important implications regarding the use of self-evaluation as a resourceefficient CBT competence assessment methodparticularly in training. The changing proportion of agreement across training supports previous assertions that self-evaluation is not an appropriate stand-alone competence assessment for trainees (Rozek et al, 2018). Rather, selfassessment appears to be more appropriate as a self-reflective learning tool (Waltman et al, 2016), with trainees' understanding of their own skill becoming more accurate with repeated comparison to expert ratings and with increasing experience.…”
Section: Discussionsupporting
confidence: 73%
“…Comparison of trainees' self-ratings and expert ratings of competence for a single session during training (Rozek et al, 2018) and towards the beginning and end of training (Mathieson et al, 2009) indicated trends towards agreement, with varying significance. Limited longitudinal evidence indicates that while there is considerable variability in the strength of the relationship between self and expert ratings, agreement tends to improve across training (Loades and Myles, 2016;McManus et al, 2012).…”
Section: Self-assessment Of Competence In Cbt Traineesmentioning
confidence: 93%
See 3 more Smart Citations